ANALISIS KEMAMPUAN PENALARAN DAN KOMUNIKASI MATEMATIS DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH MATEMATIKA PADA SISWA KELAS VII SMPN 2 JEMBER - Fuada, Maya Sofiatul; Sunardi, Sunardi; Setiawan, Toto Bara (Department of Mathematics Education , University of Jember, 2017)
Abstract. Mathematical reasoning ability is the ability to think through math problems logically in order to get a conclusion or a solution. Mathematical communication ability is the ability to present mathematical ideas through notations, symbols, or images. This research aimed to describe student’s mathematical reasoning and communication ability in solving math problems. The type of this research is descriptive qualitative research with 9 students of class VII-A SMPN 2 Jember as the subjects who have categorized according to the strudent’s ability of mathematics (high, moderate, and low). Methods of data collection in this research are test method and interviews method. Based on the results of the mathematical reasoning and communication ability’s test reinforced by interviews, the ability of student’s mathematical reasoning and communication to solve math problems are varied. For the mathematical reasoning ability, from 3 students that have a high mathematical ability, 2 strudents have a very good mathematical reasoning ability and 1 student has an enough mathematical reasoning ability. From 3 students that have a moderate mathematical ability, 2 strudents have a good mathematical reasoning ability and 1 student has an enough mathematical reasoning ability. From 3 students that have a low mathematical ability, 3 students have less mathematical reasoning ability. For the mathematical communication ability, from 3 students that have a high mathematical ability, 2 strudents have a very good mathematical communication ability and 1 student has an enough mathematical communication ability. From 3 students that have a moderate mathematical ability, 1 strudents has a very good mathematical communication ability and 2 student have a good mathematical communication ability. From 3 students that have a low mathematical ability, 1 student has an enough mathematical communication ability and 2 students have less mathematical communication ability. It can be concluded that the higher the student’s mathematical ability, the higher the student’s reasoning and communication ability in solving math problem. Keywords: Mathematical Reasoning Ability, Mathematical Communication Ability, Mathematic’s Problem Solving.